The Peculiarities of the Prevalence of Tobacco Smoking among Schoolchildren in Ukraine - N.S. Polka; O.V. Dobrianska; O.I. Turos; I.V. Dardynskaia; D. Zeingler (Zaslavsky O.Yu., 2016)
In the European Region, 40 % of poor health and premature deaths are caused by three avoidable risk factors: smoking, alcohol and traffic accidents (which are in turn frequently caused by alcohol). Among the WHO regions, Europe has the highest prevalence of tobacco smoking among both adults (28.0 %) and adolescents (19.0 %).In the period from 1999 to 2014 three series of international surveys (ESPAD, GYTS, and HBSC) were carried out in Ukraine, which contained, inter alia, questions on smoking. All interviews were conducted among children of different school ages. The results of the survey of schoolchildren conducted in 2010-2011, demonstrated that Ukraine continues to occupy a leading position in terms of smoking (3rd place after the Czech Republic and Italy). The following negative tendencies have been revealed: 28.8 % ever smokers initiated smoking before age ten; 3.7 % always have or feel like having a cigarette first thing in the morning; besides cigarettes, cigars, cigarillos, mini-cigars become more popular among the adolescent smokers (to 7.2 %); 55.3 % of never smokers are likely to initiate smoking next year; 19.2 % have an object with a cigarette brand logo. In addition to tobacco, alcohol is the second common habit among today's teenagers. According to the Institute for Social and Forensic Psychiatry and Toxicology, Ministry of Health of Ukraine, 22 % of pupils and students drink alcohol on a daily basis or several times a week. The high prevalence of smoking and alcohol use among children and adolescents in Ukraine requires the development and introduction of new effective preventive measures aimed at the formation of health behavior in young people. It is also important to start preventive measures in advance of the onset of risk behavior.